TheRelationship between Charisma Leadership and Quality Culture in Nursing, Phrae Hospital - Kaewkla, Sasitorn; Hingkanont, Poonsuk (NU Journal of Nursing and Health Sciences, 2019)
The purposes of this descriptive research were 1) to study level of Charismatic Leadership of the Head Nurse. 2) to find the Quality Culture in Nursing and 3) to explor the relationship between charismatic leadership of Head Nurse and Quality Culture in Nursing, phrae hospital. The sample comprised 209 professional nurses, who practice in phrae hospital and no nursing management position from 20 nursing services unit. Stratified Random Sampling and Simple Random Sampling technique were used for selecting the sample. The research instrument was divided into three parts of questionnaires: 1) persondata, 2) Charismatic Leadership of Head Nurse, 3) Quality Culture in Nursing. These tools were tested for Content validity. The Cronbach 's alpha reliability coefficients of part 2 and 3were 0.99 , 0.98 respectively. Data were analyzed by using percentage, mean, standard deviation, and the Pearson's product moment correlation coefficient. The research findingswere as follows. 1) Professional nurse rated their charismatic leadership of Head Nurse was high level ( = 3.76, SD = 0.66) 2) TheQuality Culture in Nursing was high level ( = 3.88, SD = 0.52) 3) There was statistical significant positive correlation at the high level between Charismatic Leadership of Head Nurse and Quality Culture in Nursing, phrae hospital (r = 807, p <.01)